Symbolic Resistance of the Subaltern in Palestine in the Novel Rijāl fī Asy-Syams by Ghassan Kanafani: Postcolonial Approach of Gayatri C. Spivak: Al-Muqāwamah ar-Ramziyyah li al-Fa’ah al-Muḥtammashah fī Filasṭīn fī Riwāyat Rijāl fī asy-Syams li Ghassān Kanafānī: al-Manhaj Mā Ba‘da al-Isti‘mār li Gayatri Spivak - Muhammad Nazar; Sindy Febrianisa; Siti Karomah (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2026)
This study aims to identify the forms of colonial domination over the subaltern in Palestine and to reveal the symbolic resistance of the subaltern against colonialism in the novel Rijāl Fī Asy-Syams by Ghassan Kanafani. The central issue in the novel concerns the silencing of subaltern voices by the upper-class society in Palestine. This research is a library research employing a qualitative approach. The study adopts Gayatri C. Spivak’s postcolonial theory as its analytical framework. The data consist of words, phrases, and sentences related to symbolic resistance found in the novel Rijāl Fī Asy-Syams. Data collection techniques include reading and categorizing data in accordance with the research focus. Data analysis was conducted through reading, describing, interpreting, and drawing conclusions. The findings of this study reveal seven forms of domination carried out by the upper class, including those in power in Palestine. These are economic, ideological, religious, social, gender-based, capitalist, and political domination. يهدف هذا البحث إلى اكتشاف أشكال هيمنة الاستعمار على الفئات الدنيا (السوبالترن) في فلسطين، وكشف أشكال المقاومة الرمزية التي تقوم بها هذه الفئات ضد الاستعمار في رواية